Improving the quality of survivorship for older adults with cancer. Issue 16 (12th May 2016) - Mohile, Supriya G.; Hurria, Arti; Cohen, Harvey J.; Rowland, Julia H.; Leach, Corinne R.; Arora, Neeraj K.; Canin, Beverly; Muss, Hyman B.; Magnuson, Allison; Flannery, Marie; Lowenstein, Lisa; Allore, Heather G.; et al.
Abstract : In May 2015, the Cancer and Aging Research Group, in collaboration with the National Cancer Institute and the National Institute on Aging through a U13 grant, convened a conference to identify research priorities to help design and implement intervention studies to improve the quality of life and survivorship of older, frailer adults with cancer. Conference attendees included researchers with multidisciplinary expertise and advocates. It was concluded that future intervention trials for older adults with cancer should: 1) rigorously test interventions to prevent the decline of or improve health status, especially interventions focused on optimizing physical performance, nutritional status, and cognition while undergoing cancer treatment; 2) use standardized care plans based on geriatric assessment findings to guide targeted interventions; and 3) incorporate the principles of geriatrics into survivorship care plans. Also highlighted was the need to integrate the expertise of interdisciplinary team members into geriatric oncology research, improve funding mechanisms to support geriatric oncology research, and disseminate high‐impact results to the research and clinical community. In conjunction with the 2 prior U13 meetings, this conference provided the framework for future research to improve the evidence base for the clinical care of older adults with cancer. Cancer 2016;122:2459–68 . © 2016 American Cancer Society . Abstract : Research priorities for older adults with cancer include the development and implementation of intervention trials. Trials for older adults with cancer should: 1) rigorously test interventions to prevent the decline of or improve health status, especially interventions focused on optimizing physical performance, nutritional status, and cognition while undergoing cancer treatment; 2) use standardized care plans based on geriatric assessment findings to guide targeted interventions; and 3) incorporate the principles of geriatrics into survivorship care plans.